Impact of Left-Digit Age Bias in the Treatment of Localized Prostate Cancer. Issue 5 (28th November 2022) - Brant, Aaron; Lewicki, Patrick; Wu, Xian; Sze, Christina; Johnson, Jeffrey P.; Basourakos, Spyridon P.; Arenas-Gallo, Camilo; Shoag, Daniel; Barbieri, Christopher E.; Zaorsky, Nicholas G.; Shoag, Jonathan E.
Abstract : Purpose: Left-digit bias is a phenomenon in which the leftmost digit of a number disproportionately influences decision making. We measured the effect of left-digit age bias on treatment recommendations for localized prostate cancer. Materials and Methods: We included men with clinically localized prostate adenocarcinoma in Surveillance, Epidemiology, and End Results from 2004 to 2018 and the National Cancer Database from 2004 to 2016. Primary outcomes were recommendations for radiation therapy and radical prostatectomy. Regression discontinuity was used to assess whether age increase from 69 to 70 years was associated with disproportionate changes in treatment recommendations. Results: In Surveillance, Epidemiology, and End Results, discontinuities were found in the proportion of patients recommended for radiation among the entire cohort (effect size 2.2%, P < .01) and among patients with Gleason 6 (1.6%, P < .01), Gleason 7 (2.5%, P < .01), and Gleason ≥8 (2.1%, P < .01) cancer, while the proportion recommended for prostatectomy decreased in the entire cohort (−1.4%, P < .01) and in patients with Gleason 7 cancer (−2.4%, P < .01). In the National Cancer Database, discontinuity from age 69 to 70 was found in recommendations for radiation in the entire cohort (effect size: 3.1%, P < .01) and in patients with Gleason 6 (2.2%, P < .01), Gleason 7 (4.0%, P < .01), and Gleason ≥8 (2.3%, P < .02) cancer, while the proportion recommended for prostatectomy decreased at this cutoff in the entire cohort (effect size: −2.7%, P < .01) and patients with Gleason 6 (−2.2%, P < .01) and Gleason 7 (−3.7%, P < .01) cancer. Conclusions: In patients with localized prostate cancer, left-digit age change from 69 to 70 was associated with disproportionately increased recommendations for radiation and decreased recommendations for prostatectomy.